Implementación del proceso contable a la Ferretería "Flor" en la ciudad de Loja, periodo 2023. - Guaman Salinas, Diana María (2024)
The Curricular Integration Work called Implementation of the accounting process to the hardware store “Flor” in the city of Loja, period 2023, was developed in order to provide management with a clear understanding of the economic-financial situation of the business allowing to determine whether it has generated profits or losses during the period, what are their real values in their inventories, detect their obligations helping the owner to make better decisions that lead to the proper functioning of the hardware store. In order to achieve the objectives set out in the work, we proceeded to prepare the plan and manual of accounts with the proper codes and instructions that will allow the proper use of each one, then the physical count of the inventory, the verification of the assets and their obligations were carried out, obtaining the following balances: assets amounting to $266,777.54, liabilities $250.12 and shareholders' equity $266,527.42 recorded in the initial statement of financial position, subsequently, all the existing documentation of the transactions carried out during the first half of 2023 is organized chronologically in order to prepare the memorandum of operations and continue with the recording in the journal, the accounts are consecutively transferred to the general ledgers, determining the debit or credit balances, and the trial balance is then prepared, followed by a worksheet determining the adjustments to the expense and cost accounts. Finally, the profit and loss statement, the statement of financial position and the income statement are prepared. Lastly, the conclusions of the result are established, determining that a loss of $10,090.12 was incurred due to poor cash management and a lack of knowledge in the use of banking operations. These results will help the owner take corrective measures to improve the business.